Gas production kinetics and in vitro degradability of tannin-containing legumes, alfalfa and their mixtures - Lagrange, Sebastian Pablo; Lobón Ascaso, Sandra; Villalba, Juan Jose (Elsevier, 2019)
The aim of this study was to determine in vitro ruminal degradability and gas production kinetics of sainfoin (Onobrichis viciifolia; SF), birdsfoot trefoil (Lotus corniculatus; BFT), alfalfa (Medicago sativa L.; ALF) and their binary or trinary mixtures using the gas production technique. The proportions in the mixtures represented: (1) those selected by lambs in a free-choice experiment (70:30 and 50:35:15 ratios for binary and trinary combinations, respectively), or (2) equal proportions (50:50 or 33:33:33 ratios for binary or trinary mixtures, respectively). Organic matter digestibility was greater in ALF and BFT than in SF (0.791 and 0.796 vs 0.751; P < 0.05) and this variable decreased as the proportion of SF in the binary mixtures increased. ALF showed greater (P < 0.05) gas production rates (RMax = 17.7 ml h−1) than BFT (16.5 ml h−1) or SF (12.9 ml h−1), reaching half of the asymptote of gas production (Parameter B = 7.3, 7.0 and 9.5 h, respectively) and maximum gas production rates at earlier times (2.4, 2.6 and 3.0 h, respectively; P < 0.05). The potential gas production (Parameter A) was ALF (210.6 ml) > SF (198.3 ml) > BFT (187.6 ml) (P < 0.05), and gas production rates decreased relative to pure ALF as the proportions of SF or BFT increased in the mixtures (P < 0.05). The presence of two or three species in the substrate did not lead to positive associative effects. Nevertheless, lambs’ preferred mixtures exhibited greater gas production rates and lower times to reach half potential gas production than mixtures formed with equal parts of each of the species (P < 0.05). Thus, mixing alfalfa with sainfoin and/or birdsfoot trefoil in a diet at a 70:30 ratio may allow sheep to maintain fermentability values as high as pure alfalfa while ingesting a diverse diet with some bioactives (e.g., condensed tannins) that provide benefits to the internal environment such as reduced bloat and ammonia formation in the rumen, as well as advantages related to dietary diversity in generalist herbivores like improvements in food intake due to reductions in sensory-specific satiety.